Strategic Enablers of ROI in Data Driven Marketing: The Role of Leadership, Culture, and BI Maturity - Widayat, Tri Agung; Toja, Andi Batari (Indonesian Scientific Publication, 2025)
This study investigates how data-driven marketing practices influence return on investment (ROI), focusing on the organizational enablers that shape their effectiveness. While the rapid growth of big data and analytics offers firms new opportunities, many struggle to translate these resources into measurable financial outcomes. This research addresses this gap by examining how leadership orientation, cultural readiness, and business intelligence (BI) maturity enhance the effectiveness of data-driven strategies in improving ROI. Using a mixed-methods approach, the study combines survey data with illustrative case studies to uncover how firms align data strategies with performance outcomes. Case evidence, such as Hugo Boss’s €15 million investment in data infrastructure, is used to complement the quantitative results and illustrate practical relevance. Findings show that predictive analytics and self-service BI can substantially increase ROI compared to traditional marketing methods. Their effectiveness is strengthened when supported by transformational leadership, a strong data culture, and organizational learning. Moreover, firms with mature BI systems demonstrate greater agility in responding to market changes, while competitive industry conditions further amplify the benefits of data-driven strategies. This study contributes a comprehensive model linking data strategies, organizational enablers, and financial performance. It offers practical insights for managers seeking to maximize the value of analytics investments through strategic alignment, cultural transformation, and committed leadershi.